Solubility properties and diffusional extraction behavior of natamycin from streptomyces gilvosporeus biomass - Zeng, X.; Danquah, Michael; Jing, K.; Woo, M.; Chen, X.; Xie, Y.; Lu, Y. (2013)
Natamycin is a type of polyene macrolide antibiotic and has been produced in submerged microbial cultures of some natural Streptomyces strains. Natamycin extraction from cellular biomass is greatly affected by the molecular and solubilization characteristics of the extraction solvent, and this is a major reason for the routine attainment of low volumetric titers, resulting from sparing natamycin solubility. In this work, a series of experiments were conducted to investigate the solubility of natamycin in some selected organic solvents in order to assess the influence on natamycin extraction yield. Natamycin showed the highest solubility in 75% aqueous methanol under the conditions of pH 2, 30°C and 1 atm. Furthermore, the extraction of natamycin using 75% aqueous methanol was performed and the highest extraction yield of 45.7% was obtained under pH 2. A mathematical model derived from Fick's law of the biomolecular diffusion process was developed to fit the experimental kinetic data of natamycin extraction.